2009
DOI: 10.1002/jms.1564
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase fragmentation of protonated C60‐pyrimidine derivatives

Abstract: Electrospray ionization mass spectrometry/mass spectrometry (ESI/MS/MS) and multiple stage mass spectrometry (MSn, n > 2) were used in the positive ion mode, with two different types of mass spectrometers, a quadrupole time-of-flight and an ion trap, to characterize two sets of different types of C60-aminopyrimidine exohedral derivatives. In one set, the pyrimidine moiety bears an amino acid methyl ester residue, and in the other the pyrimidine ring is part of a nucleoside-type moiety, the latter existing as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…An ion at m/z 752 corresponding to [C 60 S] + is also observed in the fragmentation of thiazolidine fullerene derivatives. Different C 60 ‐aminopyridine exohedral derivatives have been studied showing two different fragmentation pathways depending on the reaction used for their preparation …”
Section: Introductionmentioning
confidence: 99%
“…An ion at m/z 752 corresponding to [C 60 S] + is also observed in the fragmentation of thiazolidine fullerene derivatives. Different C 60 ‐aminopyridine exohedral derivatives have been studied showing two different fragmentation pathways depending on the reaction used for their preparation …”
Section: Introductionmentioning
confidence: 99%
“…During the course of our investigations on the homo-and heterocyclic fullerene cycloadducts, we have observed that the molecular odd-electron ions generated under ESI conditions and negative mode of detection from substituted isoxazolinofullerenes [25] . On the other hand, the retro-Diels-Alder reaction (RDA) is a wellknown process, which can be generated in a mass spectrometer [26][27][28], and is one of the most investigated spectrometric process in the fullerene chemistry [29][30][31]. A RDA process is observed when substituted tetrahydroquinazolinofullerenes undergo a fragmentation forming as the only product ion the [60]fullerene [32].…”
Section: Introductionmentioning
confidence: 99%
“…Isomer differentiation using ESI-MS/MS can be accomplished if the product ions of the isomers, positional, diastereoisomers and others, have different m/z values or if they have the same m/ z values, but different relative abundances. 93,121 In general, isomer differentiation by ESI-MS/MS is not straightforward and it is oen based on the formation of adducts, complexes or derivatized species, either in the source 129,130 or before the introduction into the mass spectrometer and in many instances, multiple stage mass analysis MS n (n > 2) is required. [131][132][133] Two b-(aminomethyl)gallium(III) T F PC isomeric derivatives 42A and 42B (Fig.…”
Section: Corrole Isomer Differentiation By Esi-msmentioning
confidence: 99%
“…Most of the reported papers on this topic describe the use of ESI-MS in the characterization of corroles, especially via accurate mass measurements, 58,89,[105][106][107][108][109][110][111][112][113][114][115] although a few studies of their gasphase chemistry, using this technique, have been published. 54,80,104,[116][117][118][119][120][121] These included the structural differentiation of corrole isomers by techniques such as TWIM-MS (travelling wave ion mobility mass spectrometry) [118][119][120] and the investigation of their gas-phase coordination chemistry. 117 MALDI has been less used, as for instance in the radical induced fragmentation of amino acid ester corroles, 89 along with ESI, and in the corrole titrations with uoride and cyanide anions.…”
Section: Introductionmentioning
confidence: 99%